Community health workers, community participation and community level inter-sectoral action: the challenges of implementing primary health care outreach services - Nxumalo, Nonhlanhla Lynette (My University, 2014)
Background: The recognition of growing health disparities globally and, in particular Sub-Saharan’s continued poor health outcomes, has been responded to with a call to revitalise primary health care (PHC) 30 years after the Alma-Ata Declaration. Despite some limitations, and although not the only solution, community health workers (CHWs) have been shown to be able to reduce factors that can act as barriers to accessing care. However, CHW programmes (often provided by non-governmental organisations in South Africa) have historically been poorly regulated and fragmented. The South African government has proposed to address the health inequities through a series of health system reforms. One of these has been a current attempt to strengthen PHC through the use CHWs in order to reach underserved communities. The capacity of CHWs to provide effective outreach services remains unclear. This work examined the experiences of CHWs in their efforts to improve access to care through community participation and outreach services that work across sectors. Aim: The study aimed to examine the implementation of community health worker-provided services through the comparison of three case studies in order to identify enabling and constraining factors. Methodology: A case study method was used to compare three CHW programmes. Qualitative methods such as key informant interviews, participant observations, focus group discussions and network maps, were used to collect data. A thematic content analysis was used to identify a priori and emergent themes. Results: CHWs operate in communities with multifaceted needs (food, transport, health and social welfare services) requiring a comprehensive approach. The experiences of households in this thesis illustrate the various barriers to accessing services. The success and sustainability of CHW programmes depends on the ongoing commitment of resources, including investment in quality training, supervision, mentoring and organizational support. Furthermore, government institutional contexts with poor cross-sectoral integration, conflicting departmental mandates and poor accountability constrain the efforts of CHWs at local level. Operating within a community with strong social cohesion and social capital provided an enabling environment for CHWs to mobilise the community and facilitate community participation, which is crucial for implementation of cross-sectoral outreach activities. Conclusion: The study indicates that CHWs provide services in communities that live in poverty which results in multiple problems that contribute to ill health. The study goes further to illustrate that in order to strengthen outreach services across relevant sectors, the role of central government is crucial. These findings indicate a need for greater understanding about how to strengthen institutional contexts both in government and in non-governmental organisations.
Keywords: Consumer Participation.; Primary Health Care--South Africa.; Community Health Services--South Africa.